GAME EDUKASI TEBAK GAMBAR BENDERA NEGARA MENGGUNAKAN METODE LINEAR CONGRUENTIAL GENERATOR (LCG) BERBASIS ANDROID - Karli Ramadhan; Lastri Widya Astuti; Dwi Asa Verano (UNIVERSITAS INDO GLOBAL MANDIRI)
The game is one of the entertainment media is the choice of children to relieve boredom or just for leisure. This game is not a means of entertainment, but it is a lesson to improve child development. This guessing game played in the form of image display using the following image is not moving so that the game felt static and monotonous. The development of the view of the games that begin to move with color graphics from the original form of dimensional approach. The games that will be made an interactive game. This is an interactive multimedia game with a controller that can be managed by the user, so the user can select any subsequent process of desired remedy, not menoton accompanied by images, sounds and features that attract so this game will be of interest to the game players have a number of criteria one of which is the educational game. Educational game that digital games designed for educational enrichment (support teaching and learning), using interactive multimedia technology and is expected to enhance learning to identify different countries flags. Applications developed flag game that has 10 levels of difficulty depending on each level, using a system based on Android Eclipse indigo are guessing. In the method of randomization flag was linear congruential generator (LCG). Linear congruential generator (LCG) is used to generate random numbers with uniform distribution, in the form of randomization in the state flag, the game design is intended to recognize the various state flag and its benefits for children to practice the logic ( analysis), training capacity spancial (intelligence picture), and the ability to read the game guess the state flag image, for parents like to give attention, accompanying them and monitor the child's development in the game